الحجيـة القانونيــة للبصمــة الوراثيــة في إثبـــات أو نــفي النَّســـب - عـبـد الــلاوي, سعـد (جامعة الوادي -University eloued, 2015)
يكتسي موضوع النَّسب في ظل التشريعات العربية والإسلامية أهمية بالغة، لارتباطه بعدة جوانب دينية وأخلاقية واجتماعية بل وصحية. وازدادت أهميته في ظل الاكتشافات العلمية والتطورات الطبية الحديثة. ولعل موضوع البصمة الوراثية يُعتبَر من أهم وأدق المواضيع المتصلة بالنَّسب؛ ذلك أنَّ النَّسب وفقا للقواعد الشرعية والقانونية العامة له طرق إثباته، غير أنَّ تغير البناء الاجتماعي التقليدي وتطور التقنية العلمية لاسيما في المجال الطبي، يفرض علينا ضرورة مواكبة هذه التطورات وتوظيف النظريات العلمية والأساليب العملية الحديثة في هذا المجال بالخصوص وغيره. ويأتي هذا البحث للإجابة عن كثير من الإشكالات المُعقَّدة والمتداخلة المتعلقة بمدى كفاية الطرق العامة لإثبات النَّسب، ومدى مشروعية الاستفادة من تقنيـــة البصمــة الوراثيــــــة، وحُجِّيتها القانونية في إثبات أو نفي النَّسب، وبيـــــان أهميتها ودورهــــا وأثــــرها في هذا المجــــال مقارنــــــة مــــع غيـــــرها مـــــن الـــوســــائل والطرق، في ظل أحكام قانون الأسرة الجزائري والفقــه الإسلامي وبعض التشريعات المقارنـــــة. - الكلمات المفتاحية: النَّسب، البصمة الوراثية، حجية قانونية، إثبات، نفي.Topic is of lineage in the Arab and Islamic legislation of great importance, is related to several aspects of religious, moral, social and even health. Increased importance in light of scientific discoveries and developments in modern medicine. Perhaps the issue of genetic fingerprinting of the most important topics related to more accurate proportions. The lineage in accordance with the rules of legality and legal public has a ways to proven, but that change the social construction of the traditional and the development of technical science, especially in the medical field, imposed on us the need to keep pace with these developments and recruitment of scientific theories and modern scientific methods in this area in particular and others. Comes of this research to answer many of the problems of complex and overlapping on the adequacy of public roads to prove lineage, and the legitimacy to take advantage of the technique of DNA, and Legal authentic to prove or deny lineage, and the statement of its importance and its role and its impact on paternity compared with other means under the provisions of the Algerian Family Code comparative Islamic law, and some comparative legislation
ماجستير اسرة
Keywords: : lineage, genetic fingerprinting, authoritative legal, prove, deny; النَّسب، البصمة الوراثية، حجية قانونية، إثبات، نفي.